1999
DOI: 10.1152/ajpheart.1999.277.2.h467
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of ovariectomy on calcium activation of cardiac and soleus myofilaments

Abstract: The hypothesis that ovarian sex hormone deficiency affects cardiac myofilament activation was tested. Chemically skinned ventricular trabeculae and single soleus muscle fibers were prepared from 10- and 14-wk ovariectomized and control rats. Tension-pCa (−log [Ca2+]) relations of left ventricular trabeculae and soleus fibers were compared to test whether thin filament proteins are potential sites of modulated activation. Trabeculae from ovariectomized rats exhibited a significant increase in Ca2+ sensitivity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
65
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 28 publications
13
65
3
Order By: Relevance
“…Specifically, F sex was associated with a lower myofilament sensitivity to Ca 2ϩ activation (Fig. 3A), consistent with previous reports of enhanced myofilament Ca 2ϩ sensitivity in overectomized F rats (4,46,52). F sex was also associated with a higher V slack , as measured by the slack test (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Specifically, F sex was associated with a lower myofilament sensitivity to Ca 2ϩ activation (Fig. 3A), consistent with previous reports of enhanced myofilament Ca 2ϩ sensitivity in overectomized F rats (4,46,52). F sex was also associated with a higher V slack , as measured by the slack test (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Gonadectomy in rats of either sex leads to a significantly reduced myosin ATPase consistent with the concomitant ϳ30 -40% reduction in ␣-MHC (3,38,39,52). Testosterone recovers cardiac function in gonectomized rats of either sex (39), whereas estrogen reduces myofilament sensitivity to Ca 2ϩ activation (4,46,52). Collectively, these observations imply that the sarcomeric incorporation of a differently performing myosin, such as the R403Q mutant ␣MHC, would modify myofilament performance and, in addition, in a sex-dependent manner.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…On the other hand, Ca 2+ sensitivity may remain the same although isometric force is reduced in soleus fibers of estrogen deficient ovariectomized rats 29 . Besides changes in the calcium mechanism, E2 can induce changes in the myosin filaments.…”
Section: Discussionmentioning
confidence: 94%
“…In mouse models, contractile characteristics are impaired in muscles of ovariectomized compared with sham-operated mice (16,38,39,53,65). It was suggested (41) and subsequently demonstrated that ovarian hormones influence muscle strength by directly affecting the function of contractile proteins (43,66), particularly the structure and function of myosin (38,39). Among the ovarian hormones, 17␤-estradiol (E 2 ) appears to be the key hormone, because it reverses muscle weakness and contractile protein dysfunction caused by ovariectomy.…”
mentioning
confidence: 99%